Restorasi Hukum Di Indonesia - Abu Bakar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The history shows that the collapse of a country does not occur suddenly. There is a long process that preceded it. The collapse as a process could be prevented when supported by a strong, responsive, and authoritative state leadership. Therefore, the collapse of law in a country can be regarded as the most valid sign of deteriorated leadership quality of the ruling regime in the country. A big, strong, and democratic country is always busy making the laws as commander (ahk?m al-h?kim). If the laws are consistently enforced as the commander, they would appear to be stone, sand, and cement for the robust state building. Conversely, when the laws are treated as a tool of power, they will be present as coal, oil, and fire for the destruction of the entire buildingstructures of the country itself.